Central Asia Reader - Farkhad S. Juraev (International Institute of Islamic Thought, 1995)
The collapse of the Soviet Union and the creation of new independent states has generated great interest among scholars and politicians in the history and contemporary situation in the region. Central Asia is not an exception to this case. Viewed in this light, Central Asia: The Rediscovery of History is a welcome contribution toward introducing the western scholarly community to the politics of Central Asia. The book is composed of a number of articles published by Turkic language specialists from 1904 to 1990, and of official documents from Central Asia and Azerbaijan. The integration processes of the Turkic peoples, which began during the Soviet period, are now in full force. In 1990, the heads of the Central Asian republics signed a treaty for economic and cultural cooperation. The treaty was also signed by Tajikistan, the only representative of the Indo-European family in Central Asia. The integration envisioned a united economic space between Kazakhstan, Uzbekistan, and Kyrgystan. In the 1992 and 1994 summits held in Ankara and Istanbul, Turkey and five newly independent Turkic states confirmed their desire to cooperate in the economic and political arenas. Therefore, attention to Central Asian problems and the publication of several scholarly works from this region are symbolic, to some extent, of the attention being paid to the significance of a common Turkic tradition and the possibilities of a meaningful integration in the “Great Turan.” The book begins with Ayaz Malikov’s “The Question of the Turk: The Way out of the Crisis.” This chapter actually sets the tone for the whole book by making a case for the need to attract the attention of scholarly and political circles from around the world to the problems of the Turkic nations and their suffering under Soviet rule. His statement that “our peoples do not have their own history” seems to be true, for all of the nations (not only the Turkic ones) in the former Soviet Union had to study mainly the history of the Russian state at the expense of developing their own historical consciousness. No doubt the author is right in his claims about Soviet violations of the rights of Turkic communities in Russia, especially the right to study in their own languages at schools and universities and even the right to listen to programs broadcast by western radio stations in their native languages. Arguing that the political history of the Turkic nations extends backwards for more than two thousand years (p. 4), Malikov calls for the right of Turkic peoples to seek unification without fear of being charged with advocating “Pan-Turkism” (p. 6). The author appeals for the formation of a terminological commission that will be entrusted with seeking the unification of the Turkic language. All of the other chapters-Muhammad Ali’s “Let Us Learn about Our Heritage: Get to Know Yourself,” Zeki Togan’s “The Origins of the Kazakhs and Ozbeks,” and Kahar Barat’s “Discovery of History: The Burial Site of Kashgarli Mahmud”-are attempts to prove the Turkic origins of Central Asia since antiquity. Ali’s attempt to connect the term “Turan” with the ethnic term “Turkic” by referring to the Shah-ndma of Abul Qasem Firdousi is quite novel, if not eccentric, as is his attribution of the Iranian language’s dominance in Central Asia as being the result ...